Da'wah Cultural in Yogyakarta: Transformation Tradition Art Jathilan in Java - Salsabiila, Aziizah; Algifahmy, Ayu Faiza; Safrodin, Safrodin (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This research discusses the transformation of Jathilan art in Yogyakarta as a form of cultural da'wah that integrates Islamic values into traditional Javanese art. Jathilan, which was originally known as a magical and mystical performance, has undergone an adaptation process to conform to Islamic teachings without losing its aesthetic essence and local cultural values. This transformation involves changes to performance elements, such as narration, music and costumes, by replacing magical elements with educational Islamic values. The role of the arts community, religious leaders and local communities is very important in this process, making Jathilan a relevant and easily accepted medium for preaching, especially by the younger generation. This research is a descriptive qualitative research using a phenomenological approach to understand in depth the transformation process of Jathilan art through the integration of sholawat elements. Data collection techniques in this research are observation, in-depth interviews, and documentation. The data analysis technique in this research is data reduction, presenting data in narrative form, and drawing conclusions. The results of this research show that Jathilan art is not just a performance that functions as entertainment, but also as a forum for conveying moral and spiritual messages that have a positive impact on the people who watch it. Elements of da'wah are instilled through prayer poetry, prayers and moral values contained in the performance. The existence of prayer poetry in Jathilan art provides the benefit of peace of mind and soul so that a person can avoid mental illness. Penelitian ini membahas transformasi kesenian Jathilan di Yogyakarta sebagai bentuk dakwah kultural yang mengintegrasikan nilai-nilai Islam ke dalam seni tradisional Jawa. Jathilan, yang awalnya dikenal sebagai pertunjukan bernuansa magis dan mistis, telah mengalami proses adaptasi untuk menyesuaikan dengan ajaran Islam tanpa menghilangkan esensi estetika dan nilai budaya lokalnya. Transformasi ini melibatkan perubahan pada elemen-elemen pertunjukan, seperti narasi, musik, dan kostum, dengan mengganti unsur-unsur magis menjadi nilai-nilai Islami yang mendidik. Peran komunitas seni, tokoh agama, dan masyarakat lokal sangat penting dalam proses ini, menjadikan Jathilan sebagai media dakwah yang relevan dan mudah diterima, terutama oleh generasi muda. Penelitian ini merupakan penelitian kualitatif deskriptif dengan menggunakan pendekatan fenomenologi untuk memahami secara mendalam proses transformasi kesenian Jathilan melalui integrasi unsur sholawat. Teknik pengumpulan data dalam penelitian ini yaitu observasi, wawancara mendalam, dan dokumentasi. Teknik analisis data pada penelitian ini yaitu dengan reduksi data, penyajian data berbentuk narasi, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan seni Jathilan tidak hanya sekedar pertunjukan berfungsi sebagai hiburan, tetapi juga sebagai wadah penyampaian pesan moral dan spiritual yang memberikan dampak positif pada masyarakat yang menontonnya. Unsur-unsur dakwah ditanamkan melalui syair sholawat, doa, dan nilai moral yang terkandung dalam pertunjukan. Adanya syair sholawat dalam kesenian Jathilan memberikan manfaat ketentraman hati dan jiwa sehingga seseorang terhindar dari penyakit mental.